sensitivity experiment using CESM POP2 ... - Gu, Sifan; Liu, Zhengyu (Zenodo, 2023)
CTRL.nc for control experiment. NoWind.nc: an experiment in which the North Atlantic (40N-60N) surface wind is suppressed to 1%. FB.nc : for the experiment in which the North Atlantic bottom topography is set to flat. The depth of North Atlantic between 0°N and 50°N is set to 4375-m uniformly. FB_NoWind.nc : an experiment in which the North Atlantic bottom topography is set to flat as FB.nc and the North Atlantic surface wind is suppressed to 1%. NA_0.01Wind.nc: an experiment in which the North Atlantic (north of 15N) surface wind is suppressed to 1%. 15N-45N.nc : an experiment in which the North Atlantic (15N-45N) surface wind is suppressed to 1%. 45N-60N.nc : an experiment in which the North Atlantic (45N-60N) surface wind is suppressed to 1%. 40N-50N.nc: an experiment in which the North Atlantic (40N-50N) surface wind is suppressed to 1%. 50N-60N.nc: an experiment in which the North Atlantic (50N-60N) surface wind is suppressed to 1%. Wind_NoTilt.nc: the zonal mean wind stress of CTRL is applied over ...